Pendampingan Pembukuan Sederhana dan Inovasi Produk Pangan Lokal bagi Ibu-Ibu di Desa Oinlasi - Angela Merici Minggu; Christian Daniel Manu; Yuningsih Nita Christiani (Jurnal Pemberdayaan Masyarakat, 2023)
The food business is a household-scale business with products that consumers are interested in. Food connoisseurs are not only children, but also teenagers, adults, and the elderly. The consequence that arises is that food businesses receive many orders to meet consumer needs. Jam is a type of snack that is eaten with bread. Jam products are a business opportunity for women in Oinlasi village. In terms of local raw materials, Oinlasi village has a lot of local food that can be used as the main raw material in making food product innovations. This PKM activity aims to improve the economy and increase community creativity in processing local food to be used as a household-based industrial business and market products online and carry out simple bookkeeping for every financial transaction that occurs. Partners in this case the PKK women are very enthusiastic in carrying out this activity. Many things were gained from this activity, namely: (1) partners felt that they had gained insight where they could use simple transaction recording, (2) partners felt that by innovating purple sweet potatoes and avocados, profits would increase, (3) partners only need to promote their products using online marketing.